High Temperature Testingand Noise Integration of a Buck Converter usingSilicon and Silicon Carbide Diodes. - RAHMANOV, Murat (Universiti Teknologi Petronas, 2004)
This project includes comparison of the advantages of enhanced SiC device performance at elevated temperatures over Si devices in a buck type DC/DC converter circuit. Being that elevated temperatures in a circuit have always caused energy losses and deviation in results, the manufacturers of silicon technology came up with a much more sophisticated Silicon Carbide technology which dramatically reduces the above mentioned two factors. The scope is mainly to examine thermal effects at high temperatures on the performance characteristics of the buck converter circuit, diode losses, switching losses and overall system losses. This project also includes effect of noise integrated buck converter circuit. So, comparison is being made between that of noise integrated and noiseless circuit both of which are being varied from a low temperature up to temperature of 300 Celsius. This project mainly utilizes PSPICE software to achieve the above stated results. Reasons and causes as to the increase of losses as the increase of temperature have been discussed in this project. Also the source of noise and practical ways of reducing noises in buck converter circuits is being stated in this project. Withpropertabulation and graphs of results this project enables to deeply understand Silicon Carbide technology used in buck converter circuit, which is a subject to elevated temperatures and noise.